Modification of the Ti15Mo alloy surface through TiO2 nanotube growth—an in vitro study - Rangel, André L.R. [UNESP]; Chaves, Javier A. M. [UNESP]; Escada, Ana L.A. [UNESP]; Konatu, Reginaldo T. [UNESP]; Popat, Ketul C.; Alves Claro, Ana P. Rosifini [UNESP] (SAGE Publications, 2018)
In this study, ordered and uniform TiO2 nanotubular structures were obtained on the surface of the Ti15Mo alloy by anodic oxidation. The amorphous state of TiO2 nanotubes formed under different anodization conditions was investigated. Crystallization of TiO2 into anatase phase occurs during annealing at temperatures of around 400°C, whereas anatase to rutile transformation starts around 500°C and is completed at 800°C. Phase transformations in annealed samples led to morphological changes of tubular nanostructures, suggesting that the oxide layer formed at the nanotube/substrate interface serves as nucleation sites for more stable phases of TiO2. The proliferation of fibroblasts cells under annealing conditions of 450°C, and of untreated samples (control group), was evaluated after 1, 4, and 7 days in cell culture using fluorescence microscopy images. A gradual increase in the number and size of cells was observed, indicating a non-toxic alloy. There was also better surface coverage on anodized samples compared with the untreated group; as well as increased development of the cytoskeleton in samples after anodization. The results of this study showed that the growth of TiO2 nanotubular structures associated with annealing allow better cell adhesion on the Ti15Mo alloy surface.
Keywords: cell adhesion; surface treatment; TiO2 nanotubes